(untitled) (Research, Society and Development, 2022)
Thermal analysis comprises a group of techniques to measure a physical property of a sample subjected to controlled temperature programming, including thermogravimetry (TGA), derivative thermogravimetry (DTG) and differential scanning calorimetry (DSC). The species Aniba duckei Kostermans, synonymous with Aniba rosaeodora Ducke, occurs in the Amazon and is also known as rosewood. Essential oils are complex oily aromatic liquids obtained by extraction from highly volatile aromatic plant materials as secondary metabolites. This research aimed to chemically and thermally characterize the essential oil of Aniba duckei. Gas chromatography was used for the quantification, by the external standard method, of the main component. The thermal study of the oil and the linalool standard was carried out using DSC and TG-DTG. The essential oil yield was 1.93% and the analysis by GC-MS confirmed the majority presence of linalool, with a concentration of 89.34% in the oil. The technical analysis revealed some similarity between the curves of pure linalool and essential oil, which is attributed to the high content of linalool in the oil. The differences between the boiling points and enthalpies of the linalool and oil pattern are justified by the presence of minor components, their concentrations in the oil and because they are substances of different polarities, molecular masses and intermolecular forces. The techniques proved to be efficient to characterize the oil. The results of the thermal analysis of the essential oil of the Aniba rosaeodora plant species are unprecedented, enabling the determination of linalool in by DSC.